DIAGNOSIS AND TREATMENT OF ÀMÓDI IN IFÁ DIVINATION AMONG THE YORUBA OF SOUTH WESTERN NIGERIA (2013)
Diagnosis in Ifá therapeutic practice makes a distinction between àìsàn ara(physical disease) - conditions that are diagnosable and treatable, and àmódi (somatoform disorders) - conditions that are not diagnosable and treatable using Western medicine. Studies in Ifá therapeutic practice have placed emphasis on àìsàn ara, while the diagnosis and treatment of àmódi have not been adequately addressed. This study, therefore, examines how àmódi is diagnosed and treated in Yoruba traditional medicine. Boas’ theory of Ethno-science and Husserl’s theory of Phenomenology were used to situate Ifá divination as a Yoruba therapeutic system. Using In-depth-Interviews (IDI), data were collected on the methods of diagnosis and treatment from 40 babaláwo (Ifá priests and healers) using snowball technique and 100 patients on their health conditions across Abeokuta, Akure, Ibadan and Osogbo, where there are state owned hospitals. Twenty-three àmódi patients who were informally referred from hospitals, were purposively selected from 100 patients, and with the use of Participant Observation method, the processes of diagnosing and treating these patients were observed, this varied from one day to six months post-treatment. Case-study model was used to group data, and they were assigned into categories. Data were content analysed. Ifá dídá (divination) diagnosed àmódi by revealing the disease aetiologies and prescriptions contained in Odù-ifá (Ifá verses). Ikin (sacred palm nuts)and ọ̀pẹ̀lẹ̀ (divining chain)served as primary diagnostic tools, while obì (kola nut), owó ẹyo (cowries) and egungun (animal bone) were used as secondary diagnostic tools. Àmódi was difficult to diagnose using Western tools because it manifested similar symptoms as àìsàn ara. The causes of àmódi were however located in Odù-ifá. Symptoms of àmódi had no regular pattern, one type of symptom (inú-kíkùn - stomach upset), resulted from multiple causations such as Ìjà Èsù (attack from Èsù),Èèwọ̀ (taboo), Orí (personality soul), just as one causation (Èèwọ̀), presented multiple symptoms such as, oríitúlu (migraine), egbò-àdáàjiná (skin ulcer), inú-kíkùn. The causes of àmódi include: Ìjà Èsù (as found in one patient), Èèwọ̀ (as found in four patients), Orí (as found in four patients), Ìwà búburú (bad character, such as ‘olè-jíjà - stealing’, ‘àgbèrè - adultery’, as found in seven patients), Àjẹ́ (witches, as found in four patients), Àì-kò-béèrè (lack of divination and Àjẹ́ were found in one patient) and Ìrírí ayé (life experiences, as found in three patients). Observed, treatments were in three stages and were referred to as siblings. Ẹbọ l’ ẹ̀gbọ́n (sacrifice being the oldest),treated the spiritual and psychological aspects of the patients. Òògùn/àkóse-ifál’àbúrò (medicine being younger),treated the physical aspects of the patients. And Ọgbọ́n-inú l’ọmọ iyèkan wọn lénjẹ lénjẹ, (inspiration being the youngest), complemented the other two. All the 23 patients confirmed full recovery. Besides each patient’s testimony of wellness, final divination - Ó tán nb’ókù? (Is this all or there is more?), was used as confirmatory tests. Ifá divination is a formidable diagnostic and treatment tool among the Yoruba of South Western Nigeria. Its ability to distinguish between similar symptoms of àìsàn ara and àmódi transcends the practice in Western medicine